Fatigue, depression, and quality of life in children with multiple sclerosis: a comparative study with other demyelinating diseases. (11th April 2019) - Florea, Anca; Maurey, Helene; Le Sauter, Melanie; Bellesme, Celine; Sevin, Caroline; Deiva, Kumaran
Abstract : Aim: To evaluate fatigue, depression, and quality of life (QoL) of children with multiple sclerosis and compare to other acute demyelinating syndromes (ADS). Method: Children followed in the National Referral Centre of rare inflammatory brain and spinal diseases were included in this study. The Expanded Disability Status Scale, the fatigue severity scale, the Multiscore Depression Inventory for Children, and the Pediatric Quality of Life Inventory were used for evaluation. Results: Thirty‐seven children (23 females, 14 males) were included in this study. Multiple sclerosis was diagnosed in 26 children and ADS in 11 children. Although not significant, severe fatigue was less frequently reported by patients with multiple sclerosis than children with ADS (44% vs 63%, p =0.2). Depression was reported more often in the multiple sclerosis group compared to the ADS group (24% vs 18%, p =0.6). Concerning the QoL in patients with multiple sclerosis, both parents and children reported poor emotional and school functioning. Physical and social functioning were rated as being good in both groups, and was significantly higher in the children's group ( p =0.007). Interpretation: This study highlights the importance of fatigue and depression in children with ADS and particularly in paediatric onset multiple sclerosis. Moreover, difficulties in school and emotional functioning were the main concerns for parents and children in the multiple sclerosis group which need to be taken in account during their care and treatment proposal. What this paper adds: Invisible signs such as fatigue and depression affect all forms of acute demyelinating syndromes (ADS) in children. Depression seems to be higher in children with multiple sclerosis than with other forms of ADS. Fatigue seems to be lower in children with multiple sclerosis than with other forms of ADS. Children with multiple sclerosis and their parents are most concerned with emotional and academic functioning. What this paper adds: Invisible signs such as fatigue and depression affect all forms of acute demyelinating syndromes (ADS) in children. Depression seems to be higher in children with multiple sclerosis than with other forms of ADS. Fatigue seems to be lower in children with multiple sclerosis than with other forms of ADS. Children with multiple sclerosis and their parents are most concerned with emotional and academic functioning. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Fatiga, depresión y calidad de vida en niños con esclerosis múltiple: un estudio comparativo con otras enfermedades desmielinizantes: Objetivo: evaluar fatiga, depresión y calidad de vida (CDV) de niños con esclerosis múltiple y comparar con otros síndromes desmielinizantes agudos (SDA). Metodo: Se incluyeron en el estudio los niños seguidos en el centro de referencia de enfermedades espinales y cerebrales inflamatorias raras. Se usaron para la evaluación la Escala de Estado de Discapacidad Expandida, la escala de severidad de fatiga, el inventario de puntaje múltiple de depresión para niños, y el inventario de calidad de vida pediátrico. Resultados: Se incluyeron en este estudio 37 niños (23 niñas, 14 niños). Se diagnosticó esclerosis múltiple en 26 niños y SDA en 11 niños. Aunque no fue significativo, la fatiga se reportó en menor frecuencia en pacientes con esclerosis múltiple que en niños con SDA (44% vs 63%, p= 0, 2). Se reporto con más frecuencia depresión en el grupo de esclerosis múltiple en comparación con el grupo de SDA (24% vs 18%, p= 0, 6). En lo que concierne a la calidad de vida en pacientes con esclerosis múltiple, tanto los padres como los niños reportaron funciones emocionales y escolares disminuidas. Las funciones físicas y sociales fueron puntuadas como buenas en ambos grupos, y fue significativamente más alta en el grupo de los niños. ( p= 0, 007). Interpretacion: este estudio resalta la importancia de la fatiga y la depresión en niños con SDA y particularmente con el inicio infantil de esclerosis múltiple. Además, las dificultades en la escuela y el funcionamiento emocional fueron las principales preocupaciones de los padres y los niños en el grupo de esclerosis múltiple que deben tenerse en cuenta durante el planeamiento de atención de la salud y tratamiento. Resumo: Fadiga, depressão e qualidade de vida em crianças com esclerose múltipla: um estudo comparativo com outras doenças desmielinizantes: Objetivo: Avaliar fadiga, depressão e qualidade de vida (QV) de crianças com esclerose múltipla, e comparar com outras síndromes desmielinizantes agudas (SDA). Método: Crianças acompanhadas em um centro de referência nacional de doenças inflamatórias cerebrais e espinhais raras foram incluídas no estudo. A Escala Expandidade de Estado da Deficiência, a escala de severidade da fadiga, o Inventário multiescore de depressão para crianças, e o Inventário Pediátrico de Qualidade de Vida foram usados na avaliação. Resultados: Trinta e sete crianças (23 do sexo feminino, 14 do sexo masculino) foram incluídas neste estudo. A esclerose múltipla foi diagnosticada em 26 crianças e SDA em 11 crianças. Embora não significativa, a fadiga severa foi menos frequentemente reportada por pacientes com esclerose múltipla do que em crianças com SDA (44% vs 63%, p =0, 2). A depressão foi reportada mais frequentemente no grupo com esclerose múltipla comparado ao grupo com SDA. (24% vs 18%, p =0, 6). Com relação à QV em pacientes com esclerose múltipla, pais e crianças reportaram pobre funcionamento emocional e escolar. O funcionamento físico e social foram pontuados como bons em ambos os grupos, sendo significativamente maior no grupo de crianças ( p =0, 007). Interpretação: Este estudo destaca a importância da fadiga e depressão em crianças com SDA e particularmente nos casos de esclerose múltipla de início pediátrico. Além disso, dificuldades no funcionamento escolar e emocional foram as principais preocupações dos pais e crianças no grupo com esclerose múltipla, o que deve ser levado em conta durante a proposta de cuidado e tratamento.